Antimicrobial nanostructured starch based films for packaging. (20th September 2015) - Abreu, Ana S.; Oliveira, M.; de Sá, Arsénio; Rodrigues, Rui M.; Cerqueira, Miguel A.; Vicente, António A.; Machado, A.V.
Highlights: Effect of clay and silver nanoparticles in starch nanostructured films were investigated. Silver nanoparticles were produced in situ with C30B by chemical reduction method. A low concentration of silver gave antibacterial properties and enhanced clay dispersion. Barrier properties of the nanostructured starch films were improved. The developed material demonstrate to be suitable for food packaging applications. Abstract: Montmorillonite modified with a quaternary ammonium salt C30B/starch nanocomposite (C30B/ST-NC), silver nanoparticles/starch nanocomposite (Ag-NPs/ST-NC) and both silver nanoparticles/C30B/starch nanocomposites (Ag-NPs/C30B/ST-NC) films were produced. The nanoclay (C30B) was dispersed in a starch solution using an ultrasonic probe. Different concentrations of Ag-NPs (0.3, 0.5, 0.8 and 1.0 mM) were synthesized directly in starch and in clay/starch solutions via chemical reduction method. Dispersion of C30B silicate layers and Ag-NPs in ST films characterized by X-ray and scanning electron microscopy showed that the presence of Ag-NPs enhanced clay dispersion. Color and opacity measurements, barrier properties (water vapor and oxygen permeabilities), dynamic mechanical analysis and contact angle were evaluated and related with the incorporation of C30B and Ag-NPs. Films presented antimicrobial activity against Staphylococcus aureus, Escherichia coli and Candida albicans without significant differences between Ag-NPs concentrations. The migration of components from the nanostructured starch films, assessed by food contact tests, was minor and under the legal limits. These results indicated that the starch films incorporated with C30B and Ag-NPs have potential to be used as packaging nanostructured material.